Text as Reflection of Multiple Ethnic Identity (on material of autobiographic novels by N. Mandela and P. Abrahams) - Svitlana Pilishek (Психолінгвістика, 2019)
The article deals with peculiarities of development and manifestation of multiple ethnicity of personality in conditions of polyethnic and multilingual environment that serves as a basis for transformation of both personality’s outlook and ethnic identity as a result of learning the second language. The current research is focused on studying the texts of autobiographic novels by Nelson Mandela (“A Long Walk to Freedom”) and Peter Abrahams (“Tell Freedom”) written in South African variant of English. Identification of original channels of culturally marked lexis that has been identified in the texts of autobiographies mentioned above has made it possible to confirm the facts multiple ethnicity that the authors possess. Language as a complex, evolutionary, hierarchically built megasystem undergoes changes at all levels while existing in a particular cultural and historical environment. The character and dynamics of such changes are predetermined by a range of factors including language contacts. The flexibility and cumulative character of the language system make it possible for the language to borrow culturally marked lexis from the “other” language. Such processes are predetermined by the fact that any language exists in close connection to the envorinment – the people; a language is a means of reality objectivation, a reflection of personality’s world. A personality learns another language, uses it in everyday life, absorbs elements of national cultures that are manifested in language through culturally marked lexis, builds own language picture of the world, and creates a network of multiple ethnicities that find their reflection in language. Interaction between a personality and representatives of other ethnic societies within a particular environment highlights both ethnic integrative and differentiating role of language.